Development and evaluation of a multiplex droplet digital polymerase chain reaction method for simultaneous detection of five biothreat pathogens - Du, Yipu; Yan, Ziheng; Song, Kai; Jin, Junyan; Xiao, Liting; Sun, Zhulin; Tan, Yafang; Zhang, Pingping; Du, Zongmin; Yang, Ruifu; Zhao, Yong; Song, Yajun (Frontiers in Microbiology, 2022)
Biothreat agents pose a huge threat to human and public health, necessitating the development of rapid and highly sensitive detection approaches. This study establishes a multiplex droplet digital PCR (ddPCR) method for simultaneously detecting five high-risk bacterial biothreats: Yersinia pestis, Bacillus anthracis, Brucella spp., Burkholderia pseudomallei and Francisella tularensis. Unlike conventional multiplex real-time PCR (qPCR) methods, the multiplex ddPCR assay was developed using two types of probe fluorophores, allowing the assay to perform with a common two-color ddPCR system. After optimization, the assay performance was evaluated, showing a lower limit of detection (LOD) (0.1–1.0 pg/μL) and good selectivity for the five bacteria targets. The multiplex assay’s ability to simultaneously detect two or more kinds of targets in a sample was also demonstrated. The assay showed strong sample tolerance when testing simulated soil samples; the LOD for bacteria in soil was 2 × 102–2 × 103 colony-forming unit (CFU)/100 mg soil (around 5–50 CFU/reaction), which was 10-fold lower than that of the single-target qPCR method. When testing simulated soil samples at bacterial concentrations of 2 × 103–2 × 104 CFU/100 mg soil, the assay presented a higher sensitivity (100%, 35/35) than that of the qPCR method (65.71%, 23/35) and a good specificity (100%, 15/15). These results suggest that the developed 5-plex ddPCR method is more sensitive than conventional qPCR methods and is potentially suitable for rapidly detecting or screening the five selected bacterial biothreats in suspicious samples.